The Potential of Batu City-Western Australia Partnership in the Fields of Agriculture and Livestock: Challenges and Opportunities - Dion Maulana Prasetya; Nurul Qomaria; Devi Ardiyanti; Putri Ulfa Habibah; Adila Putri; Irma Hermayanis (Universitas Muhammadiyah Malang, 2023)
The objective of this essay is to assess the possibility of collaboration between Batu City and Western Australia in the field of Agriculture and Livestock. The author employed a qualitative research methodology to investigate the collaboration between Batu City and Western Australia. The study approach adopted was descriptive, focusing on providing a detailed account of the collaboration. The primary method of data gathering involved conducting interviews with government personnel from Batu City. Additionally, secondary material was gathered from reputable websites and periodicals, and subsequently examined within the concept of the Paradiplomacy. The researchers discovered a significant potential for collaboration between the two cities. Batu City excels in producing high-quality horticultural seeds that are exported to multiple countries. However, there is a drawback in the livestock sector due to the prevalence of diseases affecting animals. As a highly developed province, Western Australia has the capability to transfer technology to Batu City in order to enhance the quality and quantity of these two sectors. Regrettably, the collaboration's potential was limited to the exploratory stage due to the Batu City Government's subpar efforts in uploading the city profile. This hindered partners from fully recognizing the potential of Batu City. Hence, it is imperative to augment the human capital of the Batu City Government and enhance its systems and administration in order to effectively engage in paradiplomacy with overseas counterparts.